SISTEM APLIKASI BERBASIS OPTIMASI METODE ELBOW UNTUK PENENTUAN CLUSTERING PELANGGAN - Elly Muningsih; Sri Kiswati (Joutica, 2018)
Customer is a very important asset for the company. Having customers who are loyal to the company is an absolute and important for the progress of the company. This study aims to help companies, especially in the online shop to create a better customer management by identifying and grouping customers into several clusters or groups to know the characteristics of their loyalty to the company. The method used in this research is K-Means method which is one of the best and most popular method in clustering algorithm. To overcome the weakness of the K-Means method in determining the number of clusters, we use the Elbow method where this method gets the comparison of the number of clusters added by calculating the SSE (Sum of Square Error) of each cluster value. This research starts from collecting the necessary data and will be processed. From total transaction data 478 then done cleaning of data and result 73 data. Then the data processed with RapidMiner software from Cluster 2 up to 10 to search the data center of each cluster. From the calculated SSE value found that the best number of clusters is 3. The end result of the research is a Visual Basic based application program that is expected to provide ease in grouping or clustering customers. Software development method using Waterfall method.